Pengetahuan Dan Sikap Perawat Berhubungan Dengan Ketrampilan Perawat Dalam Meminimalkan Kecemasan Akibat Hospitalisasi Pada Anak - Mevi Lilipory (MOLUCCAS HEALTH JOURNAL, 2020)
Hospitalization is a process that requires the child to stay and be treated in the hospital due to planned and emergency reasons to do the therapy and treatment until their return to go home. Because of treatment in the hospital, especially for pediatric patients can have an impact both of physically and psychologically including anxiety. This study aims to determine the relationship of nurses 'knowledge and attitudes with nurse's skills in minimizing anxiety due to hospitalization of children at RSUD dr. M. Haulussy Ambon July 2019. The design used in this study was a descriptive analytic survey using a cross sectional approach. The sampling technique used in this study was total sampling with the sample size in this study was 34 respondents. Statistical test results using the chi-square test obtained p-value of knowledge with nurse skills of 0.002 (p <0.05) and p-value of attitude with nurses skills of 0.015 (p <0.05). In conclusion there is a significant relationship between knowledge and attitude with the skills of nurses in minimizing the anxiety because of the hospitalization for children at RSUD dr. M. Haulussy Ambon 2019. It is recommended for the nurses to be able to increase the knowledge about psychology of children to minimize the anxiety of children. The parents need to increase the knowledge about anxiety due to hospitalization in children so that it can help minimize the anxiety experienced by children during treatment in the hospital. For further researchers,they are able to see the anxiety of children due to hospitalization by adding several variables such as knowledge and family support.Keywords: hospitalization, anxiety, nurses, skills, knowledge, attitudes